Periampullary Adenocarcinoma with Incidental Gastric Carcinoid Tumor: Report of an Extremely Rare Case - Shahriar, Shaon; Ghosh, Niloy Dipanker; Alam, Shoeb Imtiaz; Ahmed, Akhter; Akther, SM Quamrul (Journal of Shaheed Suhrawardy Medical College, 2023)
Periampullary neoplasms are a heterogeneous group of tumors arising within 2 cm of the ampulla of Vater. Neuroendocrine tumors can originate throughout the entire body from neuroendocrine cells. These neoplasms exhibit deep differences, according to their origin and biological behavior. The synchronous presence of a primary tumor in patients affected by a neuroendocrine tumor is reported in the literature; incidence is variable and the most common site is the gastrointestinal tract. Here we report a case of 68 years old female presented with jaundice, anorexia and weight loss. She was mildly anaemic. Gall bladder was palpable. There was no organomegaly. Her CT scan and MRCP revealed a growth in periampullary region. So she underwent Whipple’s procedure. Histopathological report showed synchronous presence of periampullary carcinoma and a carcinoid tumor in stomach. As the carcinoid tumor was nonfunctioning and very small in size, it was not identified in pre-operative work up. J Shaheed Suhrawardy Med Coll 2021; 13(2): 183-186